Sexual and environmental dimorphism of the incidence of significant correlations between body weight and height and foot parameters among 14-18-year-old adolescents - Mrozkowiak, Mirosław J. (Journal of Education, Health and Sport, 2018)
Introduction: The objective of this study was to show the frequency of significant correlations between body weight and height and the selected parameters of body posture within trunk in 14-18-year-old adolescents. Material and methods. The study which was conducted among randomly selected teenagers aged 14-18 years during the period of 3 years, in 6 half-year editions, enabled the author to record 2445 observations with regard to the measurement of 48 parameters describing trunk, body weight and height. The subjects involved in the study were enrolled from the Warminsko-Mazurskie region. The photogrammetric method with the phenomenon of mora projection was used to measure the selected parameters. Findings. The frequency of significant correlations between body height and the features of body posture was 21.42% and with regard to body weight it was 14.28%. The frequency of significant correlations between body height within sex was 14.28%, and concerning body weight it was 4.76%, whereas among girls the figures were 7.14% and 9.52% respectively. Conclusions 1. Among adolescents aged 14-18 years, body height revealed significantly more frequent correlations with the parameters of feet than body weight. 2. Body height was reported to reveal more frequent significant correlations with the parameters of feet than body weight among boys. As regards girls involved in the study, the frequency of these significant relationships was similar and revealed lower values. Body weight and height showed more frequent correlations with the parameters of feet in children living in towns and cities than in their counterparts from the rural environment. 3. Among boys, more frequent significant correlations between body height and the parameters of feet were observed in subjects living in the urban environment, and the correlations concerning body weight significantly differed from the percentage of the relationships regarding body height. Among girls living in the rural environment, the correlations between body height and the parameters of feet were more frequent than in the subjects living in towns, and regarding weight, these correlations were reported to be bigger in towns than in villages. The percentage of significant relationships was very low in the rural environment.